Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Melalui Online Single Submission (OSS) UMKM di Kelurahan Bendo - Delia Noor Rizkita Kisworo; Junaidi Ariansyah; Faridhatul Ismah Budiningsih; Melinda Dwi Prameswari; Hidayah Nur Imansari Devianti; Natasya Intan Ayu Pradhita; Dewi Puspa Arum (Institut Nalanda, 2023)
Legality in running a business is important for the MSMEs, one form of legality is the Business Identification Number (NIB). This Business Identification Number can be obtained by new and old businesses by registering on the OSS Republik Indonesia website. In carrying out this community service, UPNJT 2023 KKNT Group 23 helps Mbah Bendo Koi Farm MSME managing the legality of their business by managing the creation of a Business Identification Number (NIB). The goal is to increase public knowledge of the importance of business legality and NIB certificates for MSMEs